Physiological and metabolic responses during a simulated judo competition among cadet athletes - Stavrinou, P. S.; Argyrou, M.; Hadjicharalambous, M. (International Journal of Performance Analysis in Sport, 2016)
This study examined the effects of a simulated judo competition among cadet judo athletes in physiological and metabolic responses. Nine cadet judo athletes participated in the study. The simulated competition consisted of four 4-minute judo matches, separated by fifteen minutes of recovery. During each match, the athletes' attacks were recorded, and during the recovery time, concentrations of lactate (La), triglycerides (TG), and glucose (GLU) were measured. The heart rate (HR) and the rating of perceived exertion (RPE) were also obtained. The results of this study indicate the high impact multiple judo matches have in cardiovascular stress and perceived exertion and highlight the main metabolic involvement of anaerobic pathway. We conclude that the increase in blood lactate concentration is not a limiting factor in judo performance in multiple one-day judo matches. In addition, in the cadets' category, the 14-minutes interval between the matches is long enough to positively influence blood lactate clearance.